The geographical competence of the students in Japan and Philippines: A comparative analysis - Mendoza, Rizalyn J. (Animo Repository, 2002)
The Japanese and the Philippines educational systems were both influenced by the educational system in the United States of America, but the two systems developed rather differently over the decades particularly in the field of geography education. Unlike Japan where the teaching and study of geography is already institutionalized, geography education at the secondary level in the Philippines is still in the process of development.This article reports on a comparative assessment of the geographic proficiency level of high school students of Japan and the Philippines in geographic knowledge, skills, values, and attitudes. The IGU's Commission on Geographical Education International Charter objectives on the knowledge skills and values and attitudes to be developed between and among students around the world were used as the parameters to facilitate comparison. An assessment geography teachers' profile in Japan and the Philippines were also examined in order to provide background on the students' learning outcome.